2007
DOI: 10.1007/s00268-007-9050-2
|View full text |Cite
|
Sign up to set email alerts
|

Delay from Symptom Onset Increases the Conversion Rate in Laparoscopic Cholecystectomy for Acute Cholecystitis

Abstract: Background Randomized trials suggest that laparoscopic cholecystectomy should be performed on first admission for acute cholecystitis. However, this is not widely practiced, possibly because of a perceived high conversion rate. We hypothesized that delay from onset of symptoms may increase the conversion rate. Methods We performed a retrospective case note review of patients undergoing emergency cholecystectomy in a single institution between January 2002 and December 2005. We analyzed whether delay from onset… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(37 citation statements)
references
References 28 publications
3
33
1
Order By: Relevance
“…Conversion rates ranging from under 5%e30% have been reported. The predictors of the need for conversion include a duration of symptoms of more than a range of 72e96 h [44,45], a white-cell count of more than 18,000 cells/sqmm at the time of presentation [44,48,49] and an age over 60 years [44,46,47]. In the present study the average conversion rate was of 20.87% but without a high rate of bile duct injuries.…”
Section: Discussionmentioning
confidence: 77%
“…Conversion rates ranging from under 5%e30% have been reported. The predictors of the need for conversion include a duration of symptoms of more than a range of 72e96 h [44,45], a white-cell count of more than 18,000 cells/sqmm at the time of presentation [44,48,49] and an age over 60 years [44,46,47]. In the present study the average conversion rate was of 20.87% but without a high rate of bile duct injuries.…”
Section: Discussionmentioning
confidence: 77%
“…[18][19][20] Larger cohort studies with lower conversion rates of less than 10% also include LC done in an elective setting, 21 with elective surgery for the noninflamed gallbladder inevitably resulting in lower conversion rates. 20 These patients will therefore benefit from all the advantages of a laparoscopic intervention, including less postoperative pain, shorter return to normal activities, and reduced blood loss.…”
Section: Resultsmentioning
confidence: 97%
“…[18][19][20] Larger cohort studies with lower conversion rates of less than 10% also include LC done in an elective setting, 21 with elective surgery for the noninflamed gallbladder inevitably resulting in lower conversion rates. 20 These patients will therefore benefit from all the advantages of a laparoscopic intervention, including less postoperative pain, shorter return to normal activities, and reduced blood loss. 22,23 More recent studies support our findings, as they also fail to show an increase in conversion rate for early LC as opposed to delayed (>6-8 weeks) surgery 18 and certain authors even show more favorable results for early surgery.…”
Section: Resultsmentioning
confidence: 97%
“…Moreover, the definition of early operation has ranged from 2 to 4 days [13][14][15][16][17] from admission. A study by Hadad et al [18] specifically looked at timing in relation to symptom onset and concluded that delay from the onset of symptoms increases the risk of conversion. We addressed the effect of both variables of time in this study.…”
Section: Discussionmentioning
confidence: 98%